Bacillus subtilis DNA gyrase: purification of subunits and reconstitution of supercoiling activity. - Orr, E (1982)
DNA gyrase from Bacillus subtilis 168 was purified by affinity chromatography on novobiocin-Sepharose and shown to consist of two subunits, A and B, with molecular weights of 100,000 and 85,000, respectively. The B subunits, which contains novobiocin-sensitive. ATPase activity, could complement the gyrA protein of Escherichia coli. No complementation was detected between the A subunit and the E. coli gyrB protein.